Attachment-Based Family Therapy for Depressed Adolescents - Diamond, Guy S.; Diamond, Gary M. (American Psychological Association, 2014)
This text shows how to design a treatment manual and adherence measure for attachment-based family therapy (ABFT) for adolescent depression and presents data and results on the treatment's efficacy.